Enhanced Oil Recovery Processes - New Technologies 2019
DOI: 10.5772/intechopen.88140
|View full text |Cite
|
Sign up to set email alerts
|

Nanotechnology Application in Chemical Enhanced Oil Recovery: Current Opinion and Recent Advances

Abstract: Chemical enhanced oil recovery (EOR) has been adjudged as an efficient oil recovery technique to recover bypassed oil and residual oil trapped in the reservoir. This EOR method relies on the injection of chemicals to boost oil recovery. Recently, due to the limitations of the application of chemical EOR methods to reservoirs having elevated temperatures and high salinity and hardness concentrations, nanotechnology have been applied to enhance its efficiency and improve oil productivity. The synergistic combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 93 publications
0
9
0
Order By: Relevance
“…This was shaken for 2 min on an orbital shaker (Protech Model 720) after which the beaker was positioned in an ultrasonic water bath (40 kHz, 500 W). The characteristics of the ultrasonic power and measurement of the water bath can be found somewhere else (Agi et al 2018b(Agi et al , 2019a. The extraction was done for 2 h during which the bath temperature was between 27 and 35 °C.…”
Section: Experimental Testmentioning
confidence: 99%
See 1 more Smart Citation
“…This was shaken for 2 min on an orbital shaker (Protech Model 720) after which the beaker was positioned in an ultrasonic water bath (40 kHz, 500 W). The characteristics of the ultrasonic power and measurement of the water bath can be found somewhere else (Agi et al 2018b(Agi et al , 2019a. The extraction was done for 2 h during which the bath temperature was between 27 and 35 °C.…”
Section: Experimental Testmentioning
confidence: 99%
“…Hence, alternative ways to increase oil production economically are prodigiously being investigated (Agi et al 2020a, b). Hitherto, various EOR processes, such as chemical, thermal and gas, have been used to boost the recovery of oil (Guo et al 2016;Adil et al 2018;Gbadamosi et al 2019a; Responsible Editor: Santanu Banerjee * Afeez Gbadamosi gbadamosiafeezo@gmail.com; r-radzuan@utm.my 2021a, b). Chemical EOR (CEOR) technology is believed to be potentially beneficial due to the increasing expertise, rational cost of capital, functional and financial capabilities (Wang et al 2021a, b;Zhong et al 2020;Gbadamosi et al 2019b;Agi et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…To alter the rock's wettability [34], improve rheological properties [35], and lessen interfacial tension [36][37][38], NPs can be injected to EOR displacement fluids. The amount of polymer or surfactant that adheres to reservoir rock can also be decreased by using NPs [39][40][41]. In a similar vein, additional research has shown that introducing NPs into PAM can increase its thermal stability [42][43][44].…”
Section: Introductionmentioning
confidence: 98%
“…To extract the remaining hydrocarbon, a tertiary recovery technique, i.e., enhanced oil recovery (EOR) technique, is applied. Among various EOR methods (thermal, microbial, gas injection), chemical EOR is attractive for specific reservoirs [ 4 ].…”
Section: Introductionmentioning
confidence: 99%